Gemological and Spectral Characteristics of Gem-Quality Blue Gahnite from Nigeria - Yifang Chen; Junhao Zheng; Mingmei Lu; Ziqi Liu; Zhengyu Zhou (Journal of Spectroscopy)
Gem-quality blue octahedral crystalline gahnite was produced in Nigeria. This paper investigated gemological and spectroscopic characteristics by basic gemological experiments, electron probes, infrared reflectance spectroscopy, laser Raman spectroscopy, photoluminescence spectroscopy, and ultraviolet-visible spectroscopy. The results show that the refractive index (RI) of Nigerian gahnite is 1.792∼1.794, and the specific gravity is 4.45∼4.66, with no fluorescence. The main chemical composition is ZnAl2O4, accounting for 93.57%, and the rest is mainly FeAl2O4, which also contains Na, Mg, Co, Mn, Cr, Cu, Si, K, and Ca elements. The infrared spectra showed midinfrared absorption bands near 510 cm−1, 559 cm−1, and 664 cm−1 in the fingerprint region, corresponding to the Zn-O stretching vibration, bending vibration, and Al-O bending vibration, respectively. The Raman spectra showed three of the five Raman active modes of the spinel group, with characteristic Raman absorption peaks located at 418 cm−1, 508 cm−1, and 660 cm−1, corresponding to Eg, T2g(2), and T2g(3) modes, respectively, and the comparison revealed a higher degree of Zn and Al ordering in this paper for gahnite. The photoluminescence spectra show the common Cr3+-activated fluorescence splitting peaks of natural spinel, of which the 686 nm (R-line) fluorescence peak is obvious and sharp. The UV-vis absorption spectra located at 444 nm and 489 nm are the most obvious, which are caused by the d-d electron leap of TFe2+ (5E ⟶ 5T2), and the blue-gray tones of the samples are mainly caused by the spin-forbidden electronic transitions in TFe2+ and MFe2+ ↔ MFe3+; the weak absorption peak at 609 nm was determined to be associated with Co2+ by derivative spectra.